A square-planar osmium(ii) complex. Issue 40 (13th April 2017) - Abbenseth, Josh; Diefenbach, Martin; Bete, Sarah C.; Würtele, Christian; Volkmann, Christian; Demeshko, Serhiy; Holthausen, Max C.; Schneider, Sven
Abstract : Reduction of the pincer complex [Os III Cl2 (PNP)] (PNP = N(CHCHP t Bu2 )2 ) affords the isolation and full characterization of an osmium(ii ) complex with square-planar coordination geometry, i.e. [Os II Cl(PNP)]. Abstract : Reduction of the pincer complex [Os III Cl2 (PNP)] (PNP = N(CHCHP t Bu2 )2 ) affords the isolation and full characterization of an osmium(ii ) complex with square-planar coordination geometry, i.e. [Os II Cl(PNP)]. Spectroscopic, structural and magnetic data in combination with multireference computations indicate strong temperature independent paramagnetism, which arises from an energetically well separated ground state that mixes with excited states through spin–orbit coupling.